Implementasi Kebijakan Bontang Menuju Kota Layak Anak Melalui Studi Kasus Penyediaan Satuan Pendidikan Ramah Anak - Trully Tisna Milasari; Agus Prastyawan; Daryono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The government has an important role in protecting children, which is implemented through the child-friendly district (KLA) policy. In the cluster of children's rights to education, utilization of leisure time and cultural activities, fulfillment is measured by the provision of Child Friendly Education Units (SRA) in the cities of Indonesia. This study aims to analyze the implementation of KLA policy through the provision of child-friendly education units in Bontang city and what factors can hinder and support the implementation of this policy. The research used a qualitative approach, where data were collected through observation, in-depth interviews and documentation. The analysis technique used is the interactive model of analysis from Miles and Huberman, namely data reduction, data presentation and conclusion drawing. From Van Meter and Horn's policy implementation theory, policies are influenced by policy size and objectives, resources, characteristics of implementing agents, inclination/disposition, inter-organizational communication and the social, economic, political environment. The results of this study show that the program has been running quite optimally. Quantitatively, the number of SRAs increases every year, but the quality still needs to be improved. The hope is that there are SRAs in Bontang that are standardized child-friendly from the Ministry of Women's Empowerment and Child Protection (Kemen PPPA). The SRA policy, which has been implemented since 2018, is encouraged by DP3AKB in collaboration with Disdikbud and Kemenag Bontang. The benefits can be felt by various stakeholders, from schools, parents, and students in efforts to prevent and handle violence that occurs in schools. The supporting factors of the SRA policy are the existing policies/legal products related to SRA, the presence of the SRA Joint Secretariat (Sekber) team, resources related to budgets in Disdikbud, facilities in education units, the presence of CSR, and the active role of parents and school committees. As for the inhibiting factors, they come from resources related to human resources and budgets in DP3AKB, the condition of the socio-economic environment of parents and educators and education personnel in the education unit, the absence of derivatives of regional regulations in the form of perwali related to SRA, inappropriate assignments, and the absence of standardized SRA.